2008
DOI: 10.1017/s026502150700302x
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-free analgesia by continuous psoas compartment block after total hip arthroplasty. A randomized study

Abstract: Opioid-free continuous psoas compartment block seems to be an appropriate and reliable technique in providing effective postoperative analgesia at rest and during physiotherapy after total hip arthroplasty when compared to intravenous morphine/ketorolac infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Early rehabilitation decreases postoperative pain and improves function and self-efficacy [10,39]. Revised anesthesia protocols with emphasis on regional and local approach in the form of peripheral nerve blocks, PCB, LPB, and local infiltration techniques have reduced nausea and vomiting and shortened hospital stay [2,4,21,42,44,58]. Aggressive pain control with revised anesthesia protocols improves participation in postoperative rehabilitation [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early rehabilitation decreases postoperative pain and improves function and self-efficacy [10,39]. Revised anesthesia protocols with emphasis on regional and local approach in the form of peripheral nerve blocks, PCB, LPB, and local infiltration techniques have reduced nausea and vomiting and shortened hospital stay [2,4,21,42,44,58]. Aggressive pain control with revised anesthesia protocols improves participation in postoperative rehabilitation [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ambulation and functional ability were similar between groups at 6 weeks and 3 months after surgery [44]. Becchi et al [4] reported a prospective randomized study of 73 patients undergoing THA to compare opioidfree continuous psoas compartment block (cPCB) with an opioid/nonsteroidal antiinflammatory drugs continuous intravenous infusion. Both groups received spinal anesthesia for surgery.…”
Section: Aggressive Pain Management With Multimodal Approach and Revimentioning
confidence: 99%
See 1 more Smart Citation
“…administration of vagolytics (atropine, glycopyrrolate) or frequency-increasing sympathomimetics (ephedrine, dopamine, others) or negative sequelae. The postoperative incidence of bradycardia was assessed in two studies (evidence level II) [72,74] and one review [14] investigating total hip arthroplasty and did not significantly differ from either epidural nor regional anaesthesia.…”
Section: Arrhythmiamentioning
confidence: 99%
“…However, another study using postoperative epidural anaesthesia reported reduced pain scores or morphine consumption as compared to systemic analgesia [73]. However, the analgesic benefit lasted only from 8 to 48 h and had no significant influence on overall outcome [74]. The question necessarily arises whether the longer immobility with epidural anaesthesia might also have exerted a negative impact on outcome.…”
Section: Postoperative Analgesiamentioning
confidence: 99%